Analisa Tugas dan Fungsi Kepala Seksi Pemberdayaan Masyarakat dan Kesejahteraan Sosial Dalam Melayani Masyarakat Kelurahan Jati Baru Kota Padang - Muhammad Takdir; Jusmita Weriza; Riswanto Bakhtiar; Doddie Arya Kusuma; Yolanda Olivia (Jurnal Administrasi Publik dan Pemerintahan, 2024)
The Head of Community Empowerment and Social Welfare plays a role in realizing Social Welfare Development, especially in enhancing economic development through community empowerment activities and social welfare. In this context, there are Community Social Workers (Pekerja Sosial Masyarakat) who function as partners for the Subdistrict to enhance development by empowering the community. This research aims to analyze the roles and functions of the Head of Community Empowerment and Social Welfare in community empowerment in Jati Baru Subdistrict, Padang City. The study also aims to identify hindering factors and efforts made by the Head of Community Empowerment and Social Welfare in the distribution of social assistance to the community. The research utilizes a qualitative descriptive method, employing data collection techniques such as interviews, documentation, and theoretical analysis. Based on the research findings, there are several obstacles in the distribution of social assistance in Jati Baru Subdistrict, such as administrative factors resulting in uneven distribution of social assistance, and limited human resources. The conclusion drawn from this research is that the roles and functions of the Head of Community Empowerment and Social Welfare in Jati Baru Subdistrict, Padang City, play a crucial role in identifying, assisting, and improving the welfare of the community. The fair and targeted distribution of assistance is essential to help those in need meet their basic needs. This study also suggests improving the quality of human resources to help reduce overlap in efforts to improve the well-being of the community